10 Supporting ethical issues in the care of the complex child. (22nd November 2019) - Aylett, Sarah; MacNiven, Anne; Archard, Dave; Linthicum, James; Brierley, Joe
Abstract : Ethical issues are common when managing children with complex medical problems. The GOSH Bioethics team (BT) provide four specific areas of support (i) Rapid Case Reviews (R/CR) – a forum for treating teams, researchers, parents/patients to consider ethical challenges; (ii) bioethical education/training; (iii) research into paediatric bioethics and (iv) staff support. The team, independently acknowledged as the leading UK organization in Paediatic Bioethics education (IME) and in innovative ethical review (UKCEN), were awarded the 2018 International Schwager Award for Bioethics. R/CR audit: 63% children> 3 diagnoses; 91% a life–limiting condition; 81% involved > 2 specialties; 57% involved experimental therapies. Respondents highlighted BT expertise and guidance, stating that 'all parties' views (including parents) were heard' and that 'the ethical issues and child's best interests were fully addressed.' Parents considered the ethics process showed the institution 'truly valued their child.' Issues have included adolescent consent & confidentiality, organ donation/transplantation and experimental treatments (e.g. CAR–T cells, conjoined–twin surgery and phage therapy) BT deliver an educational program to GOSH professionals, paediatric and other MSC students at UCL–ICH and Kings College and both UK and Erasmus/other international medical and other students. BT run medical student trainings days, end–of–life and ethical simulation sessions. Staff support aims to recognize and prevent moral distress in GOSH teams (pre–reg/other nurses & medical/AHP professionals) by providing routine and drop in support sessions and so improve staff retention and prevent 'burn out.' Existing research has produced peer–reviewed publications in Bioethics, JME, Lancet Respiratory and Archives of Diseases in Childhood. BT is (i) developing a collaborative London Paediatric Bioethics colloquium focusing on decision-support, educational forums, peer support and cross-centre guidance AND (ii) with UCL Laws, Philosophy, and Medicine a unique Paediatric Bioethics Centre to initiate and support further high-quality national and international research into key paediatric ethical issues.